Melatonin Alleviates LPS-Induced Pyroptotic Cell Death in Human Stem Cell-Derived Cardiomyocytes by Activating Autophagy - Ya Qiu; Yan Ma; Min Jiang; Sulei Li; Jibin Zhang; Haixu Chen; Mengqi Xu; Shan Gao; Lei Tian; Bo Tao; Yabin Wang; Dong Han; et al. (Hindawi Limited, 2021)
Endotoxemia in sepsis remains a problem due to a lack of effective strategies. Our previous studies have demonstrated that melatonin (Mel) protects against ischemic heart injury and arteriosclerosis. However, its role in endotoxemia-exposed cardiomyocytes remains poorly understood. This study explored, for the first time, the protective effect of Mel on the pyroptosis of human stem cell-derived cardiomyocytes (hiPSC-CMs) exposed to lipopolysaccharide (LPS). Our results showed that treatment with 1 μM or 10 μM Mel for 12 h significantly improved 1 μg/ml LPS-induced hiPSC-CM injuries, as reflected by drastically decreased LDH release and increased cell viability, which was accompanied by the overt induction of autophagy. Specifically, Mel profoundly alleviated LPS-induced cell pyroptosis, as evidenced by decreased propidium iodide (PI) and active caspase-1 double-positive cell rates; suppressed the expression of NLRP3, cleaved caspase-1 (activated form of caspase-1), and GSDMD-NT (functional N-terminal fragment of GSDMD) expression; and inhibited the production of the cleaved IL-1β and cleaved IL-18 cytokines. Additionally, double-membrane autophagosomes were observed in LPS-injured hiPSC-CMs treated with 1 μM or 10 μM Mel. The hiPSC-CMs treated with LPS exhibited considerably fewer acidic vesicles (as revealed by LAMP1 staining) and autophagosomes (as revealed by LC3-II staining); however, Mel reversed this outcome in a dose-dependent manner. Furthermore, coincubation with rapamycin (an autophagy activator) or 3-MA (an autophagy inhibitor) accentuated and attenuated the antipyroptotic actions of Mel, respectively. Collectively, our findings demonstrate that Mel shields hiPSC-CMs against pyroptosis during endotoxemia by activating autophagy.